Effect of organics and inorganics on carbon sequestration in pearlmillet-mustard cropping sequence - Khambalkar, Priyadarshani A.; Tomar, P. S.; Verma, S. K.; Gurjar, N. S. (Annals of Agricultural Research, 2016)
The field experiment was conducted from kharif 2010 to rabi 2012 at Gwalior, Madhya Pradesh on permanent plots under pearlmillet (Pennisetum glaucum [L.] R. Br. Emend. Stutz) - mustard (Brassica juncea [L.] Czern. & Coss.) cropping sequence. The study was aimed to find out the effect of addition of organics alone and their respective combinations with chemical fertilizers on different pools of organic carbon. The results showed that the very labile (CVL), labile (CL), less labile (CLL) carbon and active (ACT) pool of carbon were significantly increased in 0.3 m and 1.0 m soil depth, respectively under organic treatments as 100% N from vermicompost (@ 5t ha-1 crop-1) and 100% N from FYM (@10 t ha-1 crop-1) over the control and other fertility treatments. The highest value of non labile (CNL) and passive pool (PSV) of carbon was recorded in control by 9.2 and 9.9 Mg ha-1 for 0.3 m depth at initial period of study. Similarly, treatment receiving 25%NPK + 75% N from vermicompost recorded maximum PSV pool (21.3 Mg ha-1) of carbon for 1.0 m soil depth at the end of study. Continuous cultivation without addition of amendments depleted the total organic carbon (TOC) content in control plot by 13.4 to 12.4 and 26.6 to 25.4 Mg ha-1 for both soil depths, respectively at the end of study; whereas maximum sequestration was recorded by 18.1 and 45.4 Mg ha-1 for 0.3 and 1.0 m soil depth, respectively in treatment receiving 100% N from vermicompost.